2008
DOI: 10.1371/journal.pone.0003496
|View full text |Cite
|
Sign up to set email alerts
|

PhoP: A Missing Piece in the Intricate Puzzle of Mycobacterium tuberculosis Virulence

Abstract: Inactivation of the transcriptional regulator PhoP results in Mycobacterium tuberculosis attenuation. Preclinical testing has shown that attenuated M. tuberculosis phoP mutants hold promise as safe and effective live vaccine candidates. We focused this study to decipher the virulence networks regulated by PhoP. A combined transcriptomic and proteomic analysis revealed that PhoP controls a variety of functions including: hypoxia response through DosR crosstalking, respiratory metabolism, secretion of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(219 citation statements)
references
References 65 publications
(122 reference statements)
7
212
0
Order By: Relevance
“…Growing evidence indicates that PhoP regulates biosynthesis of sulfolipids (SL), diacyltrehaloses (DATs), and polyacyltrehaloses (PATs), and the absence of these complex lipid molecules in the phoP mutant is a major reason for the attenuated growth of the bacilli in a mouse model (5,6,8,9). More recent studies suggest that PhoP, in addition to complex lipid biosynthesis, impacts numerous aspects of M. tuberculosis physiology, including early and enduring hypoxic responses (10), regulation of ESAT-6 secretion, specific T-cell recognition during virulence regulation of the bacilli (10 -12), and pH sensing during intracellular adaptation (13). However, biochemical evidence showing the role of PhoP in transcription activation has been lacking.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…Growing evidence indicates that PhoP regulates biosynthesis of sulfolipids (SL), diacyltrehaloses (DATs), and polyacyltrehaloses (PATs), and the absence of these complex lipid molecules in the phoP mutant is a major reason for the attenuated growth of the bacilli in a mouse model (5,6,8,9). More recent studies suggest that PhoP, in addition to complex lipid biosynthesis, impacts numerous aspects of M. tuberculosis physiology, including early and enduring hypoxic responses (10), regulation of ESAT-6 secretion, specific T-cell recognition during virulence regulation of the bacilli (10 -12), and pH sensing during intracellular adaptation (13). However, biochemical evidence showing the role of PhoP in transcription activation has been lacking.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…The gene phoP encodes the transcription factor of the two-component virulence system PhoPR and the gene fadD26 is one of the 13 genes responsible for biosynthesis and export of phthiocerol dimycocerosates (PDIM), the main virulence-associated cell-wall lipids of M. tuberculosis [54][55][56]. PhoP has been shown to regulate more than 2% of M. tuberculosis genome, most of which implicated in virulence [57,58], and this regulation could be mediated through other transcription factors, for example, Whib6 of the ESX-1 system [43] or via noncoding RNAs (ncRNAs), such as the recently described mcr7 and its role in activating the TAT secretion system in MTBVAC leading to over secretion of major antigens such as the Ag85 complex [59]. Other relevant virulence genes regulated by PhoP include lipid metabolism genes (e.g.…”
Section: Mtbvac Vaccine Constructionmentioning
confidence: 99%
“…In addition, M. tuberculosis has 12 two-component regulatory systems (Tucker et al, 2007). Two of them, phoPR (Gonzalo-Asensio et al, 2008) and dosRS (devRS) (Park et al, 2003), were studied more thoroughly than others. It was shown that functional activity of the phoPR system supports the M. tuberculosis virulence by regulating the metabolism of complex lipids and the work of the ESX secretion systems (Gonzalo-Asensio et al, 2008).…”
Section: Transcription Regulationmentioning
confidence: 99%
“…Two of them, phoPR (Gonzalo-Asensio et al, 2008) and dosRS (devRS) (Park et al, 2003), were studied more thoroughly than others. It was shown that functional activity of the phoPR system supports the M. tuberculosis virulence by regulating the metabolism of complex lipids and the work of the ESX secretion systems (Gonzalo-Asensio et al, 2008). The positive transcription regulator phoP was observed to induce genes under its control in a low-acid (pH 6.4) environment of mouse macrophage phagosomes (Rohde et al, 2007).…”
Section: Transcription Regulationmentioning
confidence: 99%